2017
DOI: 10.3389/fimmu.2017.01624
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing Identifies a Novel MAP3K14 Mutation in Recessive Atypical Combined Immunodeficiency

Abstract: Primary immunodeficiency disorders (PIDs) render patients vulnerable to infection with a wide range of microorganisms and thus provide good in vivo models for the assessment of immune responses during infectious challenges. Priming of the immune system, especially in infancy, depends on different environmental exposures and medical practices. This may determine the timing and phenotype of clinical appearance of immune deficits as exemplified with early exposure to Bacillus Calmette-Guérin (BCG) vaccination and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…Of note, a human homozygous loss-offunction NIK Pro565Arg variant is also linked to child death (13). A homozygous NIK Val345Met variant is associated with severe child illness (14). Thus, TEC-intrinsic NIK/IKKα pathways crucially support life in both mice and humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, a human homozygous loss-offunction NIK Pro565Arg variant is also linked to child death (13). A homozygous NIK Val345Met variant is associated with severe child illness (14). Thus, TEC-intrinsic NIK/IKKα pathways crucially support life in both mice and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Global inactivation of NIK abrogates thymic medullary development in mice, leading to autoimmune disease (11,12). Importantly, human NIK Pro565Arg and NIK Val345Met variants are linked to profound immune dysfunctions (13,14). Thus, NIK is an essential regulator of the immune system in both mice and humans.…”
mentioning
confidence: 99%
“…Using an overexpression cell model to mimic the effects of the mutations, we showed that the mutation significantly impaired the ability of NIK to phosphorylate IKKα. [51] Subsequent to this finding, we identified the same mutation in another patient presenting with destructive pneumonia and hypogammaglobulinaemia. Both parents were heterozygous carriers of the mutation.…”
Section: Using Next-generation Sequencing Technologies In Clinical Sementioning
confidence: 67%
“…PIDs are challenging to diagnose because of their variable clinical presentations but, in many cases, PIDDGEN has already been able to make a definitive diagnosis only through WES. [51,92,93] One such case clearly illustrates the value of WES for diagnosis of PIDs: Patient CE, a young girl from a non-consanguineous marriage, was at two years of age diagnosed with humoral immunodeficiency after presenting with a BCG abscess on the upper leg. CE was placed on intravenous immunoglobulin replacement therapy, but developed BCG meningitis a year later.…”
Section: Using Next-generation Sequencing Technologies In Clinical Sementioning
confidence: 99%
“…3 Diagnosing peanut allergy involves diagnostic procedures including careful review of clinical reactions, peanut-specific IgE, skin prick test (SPT), and an oral peanut food challenge (FC), optimally performed using a double-blind placebo-controlled FC approach. In addition, component-resolved allergen diagnosis [4][5][6] (CRD) and possibly also peanut conjunctival allergen provocation test 7 (CAPT) may improve peanut allergy diagnosis. Testing CRD in diagnosis of peanut allergy has been found useful in assessing the likelihood of clinical allergy or cross-reactive allergic manifestations.…”
Section: To the Editormentioning
confidence: 99%